KOMPARASI REKSADANA SAHAM NASIONAL DENGAN REKSADANA SAHAM ASING - Artini, Luh Gede Sri; Darmayanti, Putu Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The purpose of the study is to compare domestic mutual funds with foreign mutual funds based on their performance when the market is bullish and when the market in a bearish state. The SPSS program is used to conduct statistical tests by independent sample t-test method that compare the achievement between 15 domestic mutual funds with the highest NAV and 15 foreign mutual funds with the highest NAV using the values of the Jensen Index and Treynor Index during the Bullish period (2018) and the Bearish period (2020). In bullish period, based on the independent sample t-test based on the Jensen index value, the performance of domestic mutual fund and foreign mutual funds are no distinction, while based on the Treynor index, it shows that the performance of domestic mutual funds is better than the performance of foreign stock funds and statistically meaningfully different. In the 2020 period (bearish trend) both of the Jensen index and the Treynor index, the performance of Domestic mutual funds is better than the performance of foreign equity funds and statistically has significant differences.